Body, sex and subversion: reflections on two queer theoreticians - Pedro Paulo Gomes Pereira; Carolina Silveira Muniz Ventura (Faculdade de Medicina de Botucatu (Unesp), 2008)
The aim of this text is to present two important queer theoreticians, Beatriz Preciado and Marie-Hélène Bourcier. After outlining their work and highlighting their definitions of sex and gender, I discuss the centrality of the body in the general economy of their works. I conclude by posing some questions, in which I emphasize the urgency of inquiring into the various vectors of differences that result from inequalities and exclusions.